Women’s Language Features Used in Dove U.S.’s YouTube Campaign Videos Targeted at Women - Lislie Angelina Setiawati; Henny Putri Saking Wijaya (Kata Kita: Journal of Language, Literature, and Teaching, 2026)
This study examines how women’s language features, based on Lakoff’s (2004) theory, are used in Dove U.S. YouTube campaigns, “My Beauty My Say.” Using a qualitative method, the study analyzes spoken utterances from five monologue-style campaign videos. Four language features were found in the campaign: lexical hedges or fillers, “empty” adjectives, intensifiers, and emphatic stress. These features are used in two main ways. In terms of function, women use these features to indicate hesitation or uncertainty, to highlight personal experiences and feelings, and to express strong emotions in a soft and polite manner. In terms of context, these features are used to describe the speakers themselves. In conclusion, Dove U.S.’s YouTube campaign videos demonstrate the use of language features that align with women’s language. Future research should include additional campaigns to provide a broader and clearer understanding of how women’s language features are used in campaign videos.